Causes of low-skilled workers’ performance in construction projects - Alhaji Ali, Zannah; Ahmad Latiffi, Aryani; Raji, Abdulazeez Umar; Waziri, Abdullahi Abba; Mohammed, Usman (Path of Science, 2017)
Skilled workers’ performance is one of the crucial aspects of labour productivity that requires proper attention for effective projects delivery in the construction industry. The level of skilled workers’ low performance has been seen to be a major factor which contributes toward inefficient construction projects productivity. Therefore, the objective of this research is to identify the causes of low-skilled workers’ performance in construction projects in the Nigeria. The objective was achieved through a structured quantitative method of questionnaire distributed to 150 respondents that comprise of active stakeholders in the Nigerian construction industry. 111 responses representing 74 % were retrieved. The data were analysed using descriptive statistics and analysis of variance (ANOVA). The finding shows that; low wages of skilled, lack of sufficient skill acquisition centres and lack of incentive schemes for skilled workers were the most significant causes of low-skilled workers’ performance in the Nigerian construction industry. The homogenous analysis indicates that there are significant differences in perception of respondents on few variables whereas majority of respondents have similarities in most of the variables. The research findings indicate the need for stakeholders in the Nigerian construction industry to provide incentives and motivate skilled workers, provide training and retraining, conducive working condition, supply of quality materials and equipment, and proper site management in order improve low-skilled workers’ performance in Nigerian construction industry towards optimal performance.